The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cancers12061393
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGFR Therapy Induces EGF Secretion by Cancer-Associated Fibroblasts to Confer Colorectal Cancer Chemoresistance

Abstract: Targeted agents have improved the efficacy of chemotherapy for cancer patients, however, there remains a lack of understanding of how these therapies affect the unsuspecting bystanders of the stromal microenvironment. Cetuximab, a monoclonal antibody therapy targeting the epidermal growth factor receptor (EGFR), is given in combination with chemotherapy as the standard of care for a subset of metastatic colorectal cancer patients. The overall response to this treatment is underwhelming and, while genetic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 38 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…Similarly, studies have found that the TME and CAFs (its main component) are among the main reasons for the development of therapeutic resistance in tumors. Cetuximab can specifically induce CAFs in colorectal cancer to secrete a large amount of epidermal growth factor, which in turn mediates MAPK signal transduction to resist cetuximab therapy, implying that targeting CAFs in the TME has potential clinical therapeutic value [69]. miR-21 is an important regulator of the activation of CAFs, and its expression is noted in tumor cells and CAFs [70].…”
Section: Cafs and Therapeutic Resistancementioning
confidence: 99%
“…Similarly, studies have found that the TME and CAFs (its main component) are among the main reasons for the development of therapeutic resistance in tumors. Cetuximab can specifically induce CAFs in colorectal cancer to secrete a large amount of epidermal growth factor, which in turn mediates MAPK signal transduction to resist cetuximab therapy, implying that targeting CAFs in the TME has potential clinical therapeutic value [69]. miR-21 is an important regulator of the activation of CAFs, and its expression is noted in tumor cells and CAFs [70].…”
Section: Cafs and Therapeutic Resistancementioning
confidence: 99%
“…Recently, disturbances in the tumor microenvironment caused by EGFR antibody have also been recognized as factors in treatment failure. Garvey et al reported that cetuximab causes cancer-associated fibroblasts to secrete more EGF and reactivate mitogen-activated protein kinase signaling in para-CRC cells [32]. Critically, it is important to understand the interaction between tumor cells and the tumor microenvironment in anti-EGFR therapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Barrios et al found out that FGF-2 could induce dormancy of breast cancer cells by activating PI3K/Akt pathway in an integrin α5β1-dependent or independent way [ 53 ]. In colorectal cancer, the administration of cetuximab could induce EGF secretion of CAFs only, exclusive of cancer cells and normal fibroblasts [ 54 ]. And Clark et al established an ex vivo hepatic microphysiological system in which they used EGF and lipopolysaccharide to activate the residual dormant breast cancer cells after chemotherapy [ 55 ].…”
Section: Main Textmentioning
confidence: 99%